Spore Production and Inoculum Formulation of Claroideoglomus Etunicatum and its Application in Maize (Zea Mays) - Rosita, Risa; Dewantara Eris, Deden; Aslan, Aslan; Imran, Zulhamsyah (SEAMEO BIOTROP, 2024)
Recently, the demand for AMF (Arbuscular Mycorrhiza Fungi) fertilizer for agriculture, plantation, and forestry in Indonesia has been very high. Meanwhile, the unavailability of an applicable AMF inoculum that's easy to use and inexpensive is one of the constraints on AMF application as a fertilizer in the field. It indicates that the best formulated inoculum must be found. The study aimed to produce AMF spores using conventional and hydroponic system, formulate the best AMF inoculum, and measure the growth response in maize (Zea mays) after applying the formulated inoculum. In the formulation stage, the study was designed using a Completely Randomized Design (CRD) with 1 factor. The factor was the type of formulation. Data were analyzed using SAS software version 9 and further tested using Duncan's Multiple Range Test (DMRT) at 5% alpha (α) level. The results reported that the conventional pot culture technique (CVNE2) treatment that had been inoculated by Claroideoglomus etunicatum produced the highest spore density amount of 350 ± 6.97 per 10 g of zeolites (P<0.05). On the other hand, the hydroponic NFT (NFTE2) treatment that had been inoculated by C. etunicatum obtained the highest AMF percent colonization amount of 98% ± 2.66% (P<0.05). Analysis of variance in the formulation stage showed TZ60F1 treatment had a significant effect (P<0.05) in increasing plant height, the number of leaves, and dry weight of Zea mays, respectively 120 cm ± 1.7 cm; 15 ± 0.84; 26.3 g ± 2.46 g in 3 months after application.